STANDAR MINIMAL NAFKAH WAJIB KEPADA ISTRI BERDASARKAN MAQASID AL-SYARI’AH - Nilhakim Nilhakim (Samawa (Sakinah, Mawaddah Warahmah), 2023)
The determination of the minimum limit of mandatory alimony for the wife needs to be studied, because there is no determination of the amount of mandatory alimony for the wife which can cause harm to the wife. However, on the other hand, if the minimum limit of mandatory maintenance for the wife is set, it will also cause harm to the husband who is unable to fulfill the obligation. The minimum limit of obligatory maintenance for the wife is not set by the Sharia text, therefore it should be studied with the approach of usul al-fiqh (maqasid al-shari'ah). So the method used in the study is an integration of deductive and inductive methods. Further analysis is done with istislahiyyah reasoning pattern. Based on this study, it was concluded that the minimum limit of mandatory maintenance for the wife is in accordance with the husband's income. Because basically the husband is obliged to protect his wife and provide all the necessities of married life according to his ability. As for the rights and obligations of husband and wife, they both bear the noble obligation to establish a household that is sakinah, mawaddah and rahmah, which is the foundation and structure of society.